Pengaruh Influencer Marketing dan Penggunaan E-Wallet terhadap Perilaku Pembelian di TikTok Shop pada Siswa Gen Z SMA Negeri 11 Kota Jambi - Febrianti, Indri; Arpizal, Arpizal; Rifki, Ahmad (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2026)
The growth of digital transactions has driven an increase in purchasing activity on the TikTok Shop. This study aims to analyze the influence of influencer marketing and e-wallet usage on purchasing behavior. This study employs a quantitative approach using an ex post facto method. Data was collected through a survey distributed to 165 respondents selected using purposive sampling and analyzed using multiple linear regression. The results indicate that influencer marketing and e-wallet usage have a positive and significant effect on purchasing behavior. This is evident from the calculated t-value of 6.810 > the critical t-value of 1.97 and a significance level of 0.000 < 0.05, indicating that these variables have a positive and significant effect. E-wallet usage also has a positive and significant effect with a calculated t-value of 3.309 > the critical t-value of 1.97 and a significance level of 0.001 < 0.05. Simultaneously, both variables have a significant effect with a calculated F-value of 31.185 > the critical F value of 3.05 and a significance level of 0.000 < 0.05. Additionally, the coefficient of determination (R²) of 27.8% indicates that the independent variables in this study account for 27.8% of the variation in purchasing behavior. These findings indicate that a combination of promotional strategies through influencers and the convenience of digital payment systems can drive an increase in purchasing activity.